Injury statistics, high risk groups, and individuals: falling through the cracks. Issue 5 (30th August 2010) - Baker, Susan P
Abstract : The Frank A Calderone Prize in Public Health, the pre-eminent award in the field, is overseen by Columbia University's Mailman School of Public Health and presented to an individual who has made 'a transformational contribution in the field of public health'. The Prize recognises an individual who has accomplished extraordinary distinction in public health and/or who has made a specific contribution which has had long-term national or global implications. On 6 May 2010, the prize was awarded to Susan Baker. This is the first time the Prize has been bestowed upon an injury control researcher.